Applied WebQual 4.0 to Evaluate SMART System in RSAB Harapan Kita - Noviandi, Noviandi (Universitas Muhammadiyah Semarang Press, 2021)
Website hospital applications are one of the technological developments that affect service quality. Therefore it is necessary to evaluate the quality of the information system provided in the hospital. The method used is webqual 4.0 with usability, information quality, and service interaction quality. Data collection was carried out used a questionnaire given to 232 health workers at RSAB Harapan Kita who interacted with the SMART application. The analysis technique used is descriptive analysis technique with a quantitative approach and cross-sectional research design. The results of this study were 74.1% stated that the quality of the application was good and 25.9% said that the quality of the application was not good, as much as 43.5% stated that the quality was sufficient when viewed from the usability dimension, 40.9% in the information quality dimension, and 40. 1% for the service interaction quality dimension. The SMART application at RSAB Harapan Kita does not yet contain clear instructions or references, does not perfectly present relevant information, and the officer states that they do not feel safe about personal information on the SMART application.